Proposta de intervenção educativa para pessoas com diabetes mellitus tipo 2 em uso de insulina : uma contribuição para a prática do autocuidado - Alves, Claudia Ruas (2015)
Introduction: Type 2 diabetes mellitus is a chronic disease with high prevalence associated to higher urbanization, population aging, obesity, inadequate diet, sedentariness, population aging and longer life span for people with this diagnosis. A challenging reality demands elaboration of new way of care, with permanent character measures of health education, performed with active participation of the subjects, with their needs, desires, limitations, fears and doubts. Objectives: Analyze educational intervention developed for people with diabetes mellitus type 2 using insulin. Propose educational intervention to be developed for people with diabetes mellitus type 2 using insulin. Method: Convergent care study based on the theoretical framework by Paulo Freire carried out in a Municipal Center for Specialties in Vitoria, ES, Brazil. Sample made up of individuals with type 2 diabetes mellitus, of both sexes, age ≥ 30 years, using insulin, glycated hemoglobin ≥7%, and who have had consultations with endocrinologists in the past twelve months. The convergence group was made up to have four 90-minute meetings, one per week. The guiding questions led the discussions. The data collected were analyzed and interpreted in the light of the used methodological framework and French discourse analysis. This study was approved by the Research Ethics Committee at the Health Sciences Center at Federal University of Espírito Santo (UFES), Brazil, under registration number 833.871. Results: They are presented in two manuscripts. The first one approaches the analysis of discourse fragments of 12 participants — ten women and two men — with average age of 63. The questioning dialogues showed that eating and exercise were a significant theme among the individuals. This poses a challenge to nursing, which still adopts prescriptive care practice. With the data obtained from the convergence group, an educational intervention proposal was developed inspired in Paulo Freire’s emancipatory principles, which was presented in the second manuscript. A Pocket Guide designed especially to health professionals presents this proposed educational intervention and also constitutes one of the results of this study. Final considerations: Developing an educational strategy allowed participants to exchange experiences, mainly interaction, sharing ideas and thoughts about selfcare practice, promoting their empowerment and autonomy. A new path to self-care, inspired in dialoguing with active participation of subjects, can favor improved handling and effective control of type 2 diabetes mellitus, in which the nurse, as part of the healthcare team, has a relevant role in developing individual or group educational healthcare activities.